Composite adsorption catalyst for removing sulfur dioxide in flue gas and preparation process of composite adsorption catalyst

By using the composite adsorption catalyst prepared by modified activated carbon and modified wood fossil powder, the problems of limited adsorption capacity and frequent regeneration and treatment of existing activated carbon catalysts are solved, and more efficient flue gas desulfurization effect and lower production costs are achieved.

CN119838570AActive Publication Date: 2025-04-18XIAN WOZER ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510337989.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

The existing adsorption catalysts based on activated carbon have problems such as limited adsorption capacity and frequent regeneration and treatment, resulting in low processing efficiency and high cost during the flue gas desulfurization process.

Method used

The composite adsorption catalyst is used, and the raw materials for preparing the raw materials include modified activated carbon, alkaline auxiliary fillers and binders. The modified activated carbon is treated with nitrogen plasma to increase its adsorption site and structural strength, and the modified wood fossil powder is treated with swelling and etherification to improve its compatibility and adhesion.

Benefits of technology

The overall adsorption capacity and adsorption rate of the catalyst are improved, the regeneration frequency is reduced, the production cost is reduced, and the structural strength and stability of activated carbon are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838570A_ABST
    Figure CN119838570A_ABST
Patent Text Reader

Abstract

The invention discloses a composite adsorption catalyst for removing sulfur dioxide in flue gas and a preparation process of the composite adsorption catalyst, and the composite adsorption catalyst is prepared from the following raw materials in parts by weight: 40-60 parts of modified activated carbon; 10-30 parts of an alkaline auxiliary filler; 5-10 parts of an adhesive; wherein the modified activated carbon is obtained by carrying out nitrogen plasma treatment on composite activated carbon, and the composite activated carbon is prepared from the following raw materials in percentage by weight: 60 to 80 percent of coconut shell fiber powder, 10 to 18 percent of attapulgite clay and 8 to 25 percent of modified wood fossil powder. The modified activated carbon in the composite adsorption catalyst is obtained by treating the composite activated carbon through nitrogen plasma, so that a large number of nitrogen-containing basic functional groups such as amino groups are introduced to the surface of the activated carbon, the pore size distribution and the pore channel structure are improved, and more adsorption sites are provided, so that the overall adsorption capacity and the adsorption rate of the catalyst are improved; therefore, the regeneration frequency and the production cost are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flue gas treatment, and in particular to a composite adsorption catalyst for removing sulfur dioxide from flue gas and a preparation process thereof. Background Art

[0002] Sulfur dioxide in flue gas is one of the main sources of air pollution. It reacts with water vapor and oxygen in the air to form sulfuric acid and sulfates, which in turn lead to the formation of acid rain. Acid rain has caused serious harm to the environment and ecosystem, such as soil acidification, water pollution, plant death, etc. Through flue gas desulfurization technology, sulfur dioxide emissions can be effectively reduced, thereby protecting the environment and ecosystem.

[0003] At present, flue gas desulfurization technology is mainly divided into wet desulfurization and dry desulfurization. In dry desulfurization, the flue gas passes through the alkaline absorbent bed or is sprayed into the flue gas flow, and contacts with the solid alkaline adsorption catalyst (such as activated carbon, metal oxides, etc.), so that sulfur dioxide reacts directly with the solid alkaline substance to generate the corresponding sulfite and sulfate. Therefore, these adsorption catalysts play a key role in the desulfurization process, which can accelerate the oxidation reaction of sulfur dioxide and improve the desulfurization efficiency.

[0004] However, existing activated carbon-based adsorption catalysts have the following defects: (1) The adsorption capacity is limited and they often have to operate at low gas velocities, which results in a larger adsorber volume; (2) During the removal process, the activated carbon loses its activity due to clogging of the surface micropores, so it needs to be regenerated frequently, resulting in low treatment efficiency and high treatment costs. Summary of the invention

[0005] The purpose of the present invention is to provide a composite adsorption catalyst for removing sulfur dioxide from flue gas and a preparation process thereof, which solves the problems of low treatment efficiency and high treatment cost caused by the limited adsorption capacity of the existing activated carbon adsorption catalyst, which requires operation at a low gas velocity and requires frequent regeneration treatment.

[0006] The present invention achieves the above-mentioned purpose through the following technical solutions: A composite adsorption catalyst for removing sulfur dioxide from flue gas, wherein the raw materials for preparing the composite adsorption catalyst include, by weight: 40-60 parts of modified activated carbon; 10-30 parts of alkaline auxiliary filler; 5-10 parts of adhesive; The modified activated carbon is obtained by treating composite activated carbon with nitrogen plasma, and the raw materials for preparing the composite activated carbon include 60-80wt% coconut shell fiber powder, 10-18wt% attapulgite clay and 8-25wt% modified wood fossil powder.

[0007] Preferably, the modified petrified wood powder is obtained by subjecting petrified wood powder to swelling and etherification treatments.

[0008] Preferably, the alkaline auxiliary filler is one or more of fly ash, mica powder, feldspar powder and slaked lime.

[0009] Preferably, the adhesive is selected from one or more of polyvinyl alcohol, polypropylene, and carboxymethyl cellulose.

[0010] The present invention also provides a preparation process of the composite adsorption catalyst for removing sulfur dioxide from flue gas, the steps comprising: S1, preparing modified wood fossil powder, and then taking dry coconut fiber powder, attapulgite clay, and modified wood fossil powder in proportion and mixing them evenly with a high-speed mixer to obtain a mixture, and taking the mixture and granulating, carbonizing, and activating it to obtain composite activated carbon; S2, taking the composite activated carbon and subjecting it to nitrogen plasma treatment to obtain modified activated carbon; S3, taking the modified activated carbon, alkaline auxiliary filler and adhesive in proportion and mixing them evenly with a high-speed stirrer to obtain a catalyst initial material; S4, taking the catalyst raw material, performing compression molding, drying, sintering, natural cooling, and packaging to obtain a composite adsorption catalyst.

[0011] Preferably, in step S1, the preparation method of the modified wood fossil powder is: (1) Swelling treatment: Take petrified wood powder and disperse it in a polyethylene glycol aqueous solution with a concentration of 0.5-2 mg / mL and a mass of 5-8 times, control the temperature to 50-60°C, and react at a stirring rate of 20-40 r / min for 6-12 hours. After the reaction is completed, filter and wash and dry the petrified wood powder obtained by filtration; (2) Etherification treatment: Take the petrified wood powder after swelling treatment, disperse it in a sodium hydroxide aqueous solution with a mass fraction of 5-8 times and 10-15%, control the temperature to 70-80°C, then add sodium chloroacetate with a mass fraction of 3-6% of the petrified wood powder for reaction for 3-5 hours, adjust the pH to neutral with acetic acid after the reaction is completed, filter, take the filtered petrified wood powder, wash and dry, and obtain the modified petrified wood powder.

[0012] Preferably, in step S1, the granulation refers to using a granulator to form particles of 1-3 mm, the carbonization refers to carbonization at 500-600° C. in a carbonization furnace for 1-2 h, and the activation refers to activation at 800-1000° C. in an activation furnace for 8-16 h.

[0013] Preferably, in step S2, the discharge voltage of the nitrogen plasma treatment is 10 kV-30 kV, the treatment time is 20-40 min, and the flow rate of the source nitrogen is 60-100 sccm.

[0014] Preferably, in step S4, the sintering refers to controlling the temperature in the sintering furnace to rise to 200-250° C. at a heating rate of 2-3° C. / min under an inert atmosphere, and keeping the temperature for 1-2 hours.

[0015] The beneficial effects of the present invention are: (1) The modified activated carbon in the composite adsorption catalyst of the present invention is obtained by treating the composite activated carbon with nitrogen plasma, so that a large number of nitrogen-containing basic functional groups such as amine groups are introduced into the surface of the activated carbon, and the pore size distribution and pore structure are improved to provide more adsorption sites, thereby improving the overall adsorption capacity and adsorption rate of the catalyst, thereby reducing the regeneration frequency and reducing the production cost.

[0016] (2) The composite activated carbon used in the present invention contains modified wood fossil powder, which can increase the structural strength and stability of the activated carbon and disperse and homogenize the etching points during plasma treatment, thereby reducing the blockage or collapse of some micropores on the surface of the activated carbon caused by plasma treatment, avoiding the loss of specific surface area, and further improving the adsorption performance of the activated carbon.

[0017] (3) The modified fossil wood powder used in the present invention is obtained by subjecting fossil wood powder to swelling treatment and etherification treatment, wherein the etherification treatment can react with a small amount of xylem hydroxyl groups remaining in the fossil wood to form new ether bonds, thereby improving the compatibility and adhesion of the fossil wood powder with the coconut shell fiber powder as a whole, and further improving the strength and stability of the activated carbon; the early swelling treatment can increase the permeability of the fossil wood, expose the xylem hydroxyl groups as much as possible, and ensure the etherification reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a SEM image of the modified activated carbon obtained after nitrogen plasma treatment in the present invention. DETAILED DESCRIPTION

[0019] The present application is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technical personnel in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0020] 1. Main raw materials and equipment: Coconut shell fiber powder: Take mature coconut shells (Hainan Province, China) and soak them in water for degumming to separate the fibers from the coconut shells. Then beat the coconut shells and use a roller beating machine to remove the coconut chaff from the fibers, remove impurities and short fibers, and finally dry them to obtain coconut shell fibers. The coconut shell fibers are crushed, graded and sieved to obtain coconut shell fiber powder with a particle size of 10-50μm.

[0021] Attapulgite clay: purchased from Hebei Guanting Building Materials Technology Co., Ltd., with a particle size of 0.1-1 μm.

[0022] Petrified wood powder: mainly petrified wood from tree trunks, purchased from the petrified wood market in Ruili City, Yunnan Province. According to infrared spectrum analysis, its main chemical composition is SiO2 and Al2O3, as well as a small amount of retained wood fiber structure. The petrified wood is crushed and sieved to obtain petrified wood powder with a particle size of 5-20μm.

[0023] Scanning electron microscope: S-4800 scanner produced by Hitachi, Ltd., Japan.

[0024] Plasma treatment equipment: CTP-2000K plasma treatment instrument produced by Nanjing Suman Plasma Technology Co., Ltd.

[0025] Specific surface area analysis equipment: Nova 4000e specific surface area pore structure analyzer produced by Quantachrome Company of the United States.

[0026] 2. Specific Implementation of Experiments

[0027] Example 1: A composite adsorption catalyst for removing sulfur dioxide from flue gas, wherein the raw materials for preparing the composite adsorption catalyst include, by weight: 40 parts of modified activated carbon, 10 parts of fly ash, and 5 parts of polyvinyl alcohol (PVA2699 is used here), wherein the modified activated carbon is obtained by treating the composite activated carbon with nitrogen plasma, and the raw materials for preparing the composite activated carbon include 80wt% of coconut fiber powder with a particle size of 10±2μm, 12wt% of attapulgite clay with a particle size of 0.2±0.01μm, and 8wt% of modified wood fossil powder with a particle size of 5±1μm; the modified wood fossil powder is obtained by subjecting the wood fossil powder to swelling treatment and etherification treatment.

[0028] The preparation process of the composite adsorption catalyst for removing sulfur dioxide from flue gas comprises the following steps: S1. Prepare modified wood fossil powder, then take dry coconut fiber powder, attapulgite clay, and modified wood fossil powder in proportion and mix them evenly with a high-speed mixer to obtain a mixture, take the mixture and make it into 1 mm particles with a granulator, then carbonize it at 500° C. for 2 hours in a carbonization furnace, and finally steam activate it at 800° C. for 16 hours in an activation furnace to obtain composite activated carbon.

[0029] Wherein, the preparation method of modified wood fossil powder is: (1) Swelling treatment: Take petrified wood powder and disperse it in a polyethylene glycol aqueous solution (PEG-800 is used) with a concentration of 2 mg / mL and a mass of 5 times the amount of the powder. The temperature is controlled at 50°C and the reaction is carried out at a stirring rate of 20 r / min for 12 h. After the reaction is completed, filter the petrified wood powder and wash and dry it. (2) Etherification treatment: Take the petrified wood powder after swelling treatment, disperse it in a sodium hydroxide aqueous solution with a mass fraction of 5 times and 15%, control the temperature to 70°C, and then add sodium chloroacetate with a mass fraction of 3% of the petrified wood powder for reaction for 5 hours. After the reaction is completed, adjust the pH to neutral with acetic acid, and finally filter. Take the petrified wood powder and wash it repeatedly with clean water, and then dry it in a dryer to obtain modified petrified wood powder.

[0030] S2. Take the composite activated carbon and subject it to nitrogen plasma treatment to obtain modified activated carbon; wherein the discharge voltage of the nitrogen plasma treatment is 10 kV, the treatment time is 40 min, and the flow rate of the source nitrogen is 100 sccm.

[0031] S3, taking the modified activated carbon, fly ash and polyvinyl alcohol in proportion and mixing them evenly with a high-speed stirrer to obtain a catalyst initial material.

[0032] S4. The catalyst raw material is pressed into a column, dried in a drying oven, sintered (in a sintering furnace, the temperature is raised to 200°C at a heating rate of 2°C / min under an inert atmosphere and kept warm for 2 hours), naturally cooled, and packaged to obtain a composite adsorption catalyst.

[0033] Example 2: A composite adsorption catalyst for removing sulfur dioxide from flue gas, wherein the raw materials for preparing the composite adsorption catalyst include, by weight: 50 parts of modified activated carbon, 20 parts of muscovite powder (800 mesh), and 8 parts of polypropylene (maleic anhydride grafted polypropylene PP18729 is used here), wherein the modified activated carbon is obtained by treating the composite activated carbon with nitrogen plasma, and the raw materials for preparing the composite activated carbon include 70wt% of coconut fiber powder with a particle size of 30±2μm, 15wt% of attapulgite clay with a particle size of 0.5±0.1μm, and 15wt% of modified petrified wood powder with a particle size of 15±1μm; the modified petrified wood powder is obtained by subjecting the petrified wood powder to swelling treatment and etherification treatment.

[0034] The preparation process of the composite adsorption catalyst for removing sulfur dioxide from flue gas comprises the following steps: S1. Prepare modified wood fossil powder, then take dry coconut shell fiber powder, attapulgite clay, and modified wood fossil powder in proportion and mix them evenly with a high-speed mixer to obtain a mixture, take the mixture and make it into 2 mm particles with a granulator, then carbonize it in a carbonization furnace at 550° C. for 1.5 hours, and finally steam activate it in an activation furnace at 900° C. for 12 hours to obtain composite activated carbon.

[0035] Wherein, the preparation method of modified wood fossil powder is: (1) Swelling treatment: Take petrified wood powder and disperse it in a polyethylene glycol aqueous solution (PEG-800 is used) with a concentration of 1 mg / mL and a mass of 6 times that of the powder. The temperature is controlled at 55°C and the reaction is carried out at a stirring rate of 30 r / min for 9 h. After the reaction is completed, filter the petrified wood powder and wash and dry it. (2) Etherification treatment: Take the petrified wood powder after swelling treatment, disperse it in a sodium hydroxide aqueous solution with a mass fraction of 6 times and 12%, control the temperature to 75°C, and then add sodium chloroacetate with a mass fraction of 5% of the petrified wood powder for 4 hours. After the reaction is completed, adjust the pH to neutral with acetic acid, and finally filter. Take the petrified wood powder and wash it repeatedly with clean water, and then dry it in a dryer to obtain modified petrified wood powder.

[0036] S2. Take the composite activated carbon and subject it to nitrogen plasma treatment to obtain modified activated carbon; wherein the discharge voltage of the nitrogen plasma treatment is 20 kV, the treatment time is 30 min, and the flow rate of the source nitrogen is 80 sccm.

[0037] S3, taking the modified activated carbon, muscovite powder and polypropylene in proportion and mixing them evenly with a high-speed stirrer to obtain a catalyst initial material.

[0038] S4. The catalyst raw material is pressed into a column, dried in a drying oven, sintered (in a sintering furnace, the temperature is raised to 220°C at a heating rate of 2.5°C / min under an inert atmosphere and kept warm for 1.5 hours), naturally cooled, and packaged to obtain a composite adsorption catalyst.

[0039] Example 3: A composite adsorption catalyst for removing sulfur dioxide from flue gas, wherein the raw materials for preparing the composite adsorption catalyst include, by weight: 60 parts of modified activated carbon, 30 parts of feldspar powder (JYOR-16 is used here), and 10 parts of carboxymethyl cellulose, wherein the modified activated carbon is obtained by treating the composite activated carbon with nitrogen plasma, and the raw materials for preparing the composite activated carbon include 60wt% of coconut shell fiber powder with a particle size of 50±2μm, 15wt% of attapulgite clay with a particle size of 1±0.1μm, and 25wt% of modified wood fossil powder with a particle size of 20±1μm; the modified wood fossil powder is obtained by subjecting the wood fossil powder to swelling treatment and etherification treatment.

[0040] The preparation process of the composite adsorption catalyst for removing sulfur dioxide from flue gas comprises the following steps: S1. Prepare modified wood fossil powder, then take dry coconut fiber powder, attapulgite clay, and modified wood fossil powder in proportion and mix them evenly with a high-speed mixer to obtain a mixture, take the mixture and make it into 3 mm particles with a granulator, then carbonize it at 600° C. for 1 hour in a carbonization furnace, and finally steam activate it at 1000° C. for 8 hours in an activation furnace to obtain composite activated carbon.

[0041] Wherein, the preparation method of modified wood fossil powder is: (1) Swelling treatment: Take petrified wood powder and disperse it in a polyethylene glycol aqueous solution (PEG-800 is used) with a concentration of 0.5 mg / mL and a mass of 8 times the amount. The temperature is controlled at 60°C and the reaction is carried out at a stirring rate of 40 r / min for 6 h. After the reaction is completed, filter the petrified wood powder obtained by filtration, wash and dry it. (2) Etherification treatment: Take the petrified wood powder after swelling treatment, disperse it in a sodium hydroxide aqueous solution with a mass fraction of 8 times and 10%, control the temperature to 80°C, and then add sodium chloroacetate with a mass fraction of 6% of the petrified wood powder for reaction for 3 hours. After the reaction is completed, adjust the pH to neutral with acetic acid, and finally filter. Take the petrified wood powder and wash it repeatedly with clean water, and then dry it in a dryer to obtain modified petrified wood powder.

[0042] S2, taking the composite activated carbon, treating it with nitrogen plasma to obtain modified activated carbon, and scanning the surface morphology with an S-4800 scanner. Figure 1 As shown, it can be seen that the surface of the activated carbon is rich in micropores, and the pore structure is complete, with basically no collapse or blockage. Among them, the discharge voltage of the nitrogen plasma treatment is 30 kV, the treatment time is 20 min, and the flow rate of the source nitrogen is 100 sccm.

[0043] S3, taking the modified activated carbon, feldspar powder and carboxymethyl cellulose in proportion and mixing them evenly with a high-speed stirrer to obtain a catalyst initial material.

[0044] S4. The catalyst raw material is pressed into a column, dried in a drying oven, sintered (in a sintering furnace, the temperature is raised to 250°C at a heating rate of 3°C / min under an inert atmosphere and kept warm for 1 hour), naturally cooled, and packaged to obtain a composite adsorption catalyst.

[0045] Comparative Example 1: A composite adsorption catalyst for removing sulfur dioxide from flue gas. The raw materials for preparing the composite adsorption catalyst include, by weight: 60 parts of modified activated carbon, 30 parts of feldspar powder (JYOR-16 is used here), and 10 parts of carboxymethyl cellulose, wherein the modified activated carbon is obtained by treating activated carbon with nitrogen plasma, and the raw material for preparing the activated carbon is coconut shell fiber powder with a particle size of 50±2μm.

[0046] The preparation process of the composite adsorption catalyst for removing sulfur dioxide from flue gas comprises the following steps: S1. Take the dried coconut shell fiber powder and make it into 3mm particles with a granulator, then carbonize it in a carbonization furnace at 600℃ for 1h, and finally steam activate it in an activation furnace at 1000℃ for 8h to obtain activated carbon.

[0047] S2. Take the activated carbon and subject it to nitrogen plasma treatment to obtain modified activated carbon; wherein the discharge voltage of the nitrogen plasma treatment is 30 kV, the treatment time is 20 min, and the flow rate of the source nitrogen is 100 sccm.

[0048] S3, taking the modified activated carbon, feldspar powder and carboxymethyl cellulose in proportion and mixing them evenly with a high-speed stirrer to obtain a catalyst initial material.

[0049] S4. The catalyst raw material is pressed into a column, dried in a drying oven, sintered (in a sintering furnace, the temperature is raised to 250°C at a heating rate of 3°C / min under an inert atmosphere and kept warm for 1 hour), naturally cooled, and packaged to obtain a composite adsorption catalyst.

[0050] Comparative Example 2: A composite adsorption catalyst for removing sulfur dioxide from flue gas, wherein the raw materials for preparing the composite adsorption catalyst include, by weight: 60 parts of modified activated carbon, 30 parts of feldspar powder (JYOR-16 is used here), and 10 parts of carboxymethyl cellulose, wherein the modified activated carbon is obtained by treating the composite activated carbon with nitrogen plasma, and the raw materials for preparing the composite activated carbon include 60wt% of coconut fiber powder with a particle size of 50±2μm, 15wt% of attapulgite clay with a particle size of 1±0.1μm, and 25wt% of petrified wood powder with a particle size of 20±1μm.

[0051] The preparation process of the composite adsorption catalyst for removing sulfur dioxide from flue gas comprises the following steps: S1. Take dry coconut shell fiber powder, attapulgite clay and wood fossil powder in proportion and mix them evenly with a high-speed mixer to obtain a mixture. Take the mixture and make it into 3 mm particles with a granulator. Then carbonize it in a carbonization furnace at 600° C. for 1 hour. Finally, steam activate it in an activation furnace at 1000° C. for 8 hours to obtain composite activated carbon.

[0052] S2. Take the composite activated carbon and subject it to nitrogen plasma treatment to obtain modified activated carbon; wherein the discharge voltage of the nitrogen plasma treatment is 30 kV, the treatment time is 20 min, and the flow rate of the source nitrogen is 100 sccm.

[0053] S3, taking the modified activated carbon, feldspar powder and carboxymethyl cellulose in proportion and mixing them evenly with a high-speed stirrer to obtain a catalyst initial material.

[0054] S4. The catalyst raw material is pressed into a column, dried in a drying oven, sintered (in a sintering furnace, the temperature is raised to 250°C at a heating rate of 3°C / min under an inert atmosphere and kept warm for 1 hour), naturally cooled, and packaged to obtain a composite adsorption catalyst.

[0055] Comparative Example 3: A composite adsorption catalyst for removing sulfur dioxide from flue gas, wherein the raw materials for preparing the composite adsorption catalyst include, by weight: 60 parts of modified activated carbon, 30 parts of feldspar powder (JYOR-16 is used here), and 10 parts of carboxymethyl cellulose, wherein the modified activated carbon is obtained by treating the composite activated carbon with nitrogen plasma, and the raw materials for preparing the composite activated carbon include 60wt% of coconut fiber powder with a particle size of 50±2μm, 15wt% of attapulgite clay with a particle size of 1±0.1μm, and 25wt% of modified petrified wood powder with a particle size of 20±1μm; the modified petrified wood powder is obtained by etherifying the petrified wood powder.

[0056] The preparation process of the composite adsorption catalyst for removing sulfur dioxide from flue gas comprises the following steps: S1. Prepare modified wood fossil powder, then take dry coconut fiber powder, attapulgite clay, and modified wood fossil powder in proportion and mix them evenly with a high-speed mixer to obtain a mixture, take the mixture and make it into 3 mm particles with a granulator, then carbonize it at 600° C. for 1 hour in a carbonization furnace, and finally steam activate it at 1000° C. for 8 hours in an activation furnace to obtain composite activated carbon.

[0057] Among them, the preparation method of modified petrified wood powder is as follows: etherification treatment: take petrified wood powder, disperse it in an aqueous sodium hydroxide solution with a mass fraction of 8 times and 10%, control the temperature to 80°C, and then add sodium chloroacetate accounting for 6% of the mass of the petrified wood powder to react for 3 hours. After the reaction is completed, adjust the pH to neutral with acetic acid, and finally filter, take the filtered petrified wood powder, wash it repeatedly with clean water, and then dry it with a dryer to obtain modified petrified wood powder.

[0058] S2. Take the composite activated carbon and subject it to nitrogen plasma treatment to obtain modified activated carbon; wherein the discharge voltage of the nitrogen plasma treatment is 30 kV, the treatment time is 20 min, and the flow rate of the source nitrogen is 100 sccm.

[0059] S3, taking the modified activated carbon, feldspar powder and carboxymethyl cellulose in proportion and mixing them evenly with a high-speed stirrer to obtain a catalyst initial material.

[0060] S4. The catalyst raw material is pressed into a column, dried in a drying oven, sintered (in a sintering furnace, the temperature is raised to 250°C at a heating rate of 3°C / min under an inert atmosphere and kept warm for 1 hour), naturally cooled, and packaged to obtain a composite adsorption catalyst.

[0061] 3. Performance Test The modified activated carbons and the final composite adsorption catalysts prepared in the above Examples 1-3 and Comparative Examples 1-3 were subjected to the following performance tests: (1) Specific surface area: The modified activated carbon samples from each experimental group were taken and their specific surface areas were measured using a Nova 4000e specific surface area and pore structure analyzer.

[0062] (2) Strength stability: Take the modified activated carbon samples from each experimental group and test their wear resistance (%) according to the standard GB / T12496.6-1999 "Test method for strength of wood activated carbon"

[0063] (3) Sulfur dioxide removal performance: The composite adsorption catalyst samples of each experimental group were taken and pre-treated with degassing (degassing at 90°C for 20 min and then degassing at 200°C for 2 h). Then, the saturated sulfur capacity was tested according to the standard GB / T7702.14-1997 "Test method for saturated sulfur capacity of coal-based granular activated carbon".

[0064] 4. Test results and analysis (1) Specific surface area: Table 1: Specific surface area test results of each experimental group

[0065] (2) Strength stability: Table 2: Wear resistance test results of each experimental group

[0066] (3) Sulfur dioxide removal performance: Table 3: Saturated sulfur capacity test results of each experimental group

[0067] It can be seen from Tables 1-3 that the modified activated carbon used in Examples 1-3 of the present invention has a large specific surface area and strength as well as excellent desulfurization performance, wherein the highest specific surface area reaches 1221.2 m 2 / g, the wear resistance can reach up to 99.1%, and the saturated sulfur capacity can reach up to 1403.4mg / g.

[0068] Comparative Examples 1-3 are all adjusted based on Example 3, wherein: In Comparative Example 1, all the raw materials for preparing activated carbon are coconut shell fiber powder, and no modified wood fossil powder is used, resulting in a significant decrease in its specific surface area and saturated sulfur capacity compared with Example 3, and a significant decrease in wear resistance. This shows that the addition of modified wood fossil powder plays an important role in maintaining the specific surface area and increasing strength stability during nitrogen plasma treatment.

[0069] In Comparative Example 2, unmodified ordinary petrified wood powder was added to the raw materials when preparing activated carbon. Its specific surface area and saturated sulfur capacity were improved compared with those of Comparative Example 2, but were still significantly inferior to those of Example 3, indicating that the modification process can improve the compatibility and adhesion of the petrified wood powder as a whole with the coconut shell fiber powder, and further improve the strength stability of the activated carbon.

[0070] In Comparative Example 3, modified fossil wood powder was added to the raw materials when preparing activated carbon (but only etherification treatment was performed without the previous swelling treatment). The specific surface area and saturated sulfur capacity were not significantly improved compared with those of Comparative Example 2, indicating that the etherification reaction could not be effectively carried out with only etherification treatment, which may be related to the dense structure of the fossil wood.

[0071] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A composite adsorption catalyst for removing sulfur dioxide from flue gas, characterized in that: The raw materials for preparing the composite adsorption catalyst include, by weight: 40-60 parts of modified activated carbon; 10-30 parts of alkaline auxiliary filler; 5-10 parts of adhesive; The modified activated carbon is obtained by treating composite activated carbon with nitrogen plasma, and the raw materials for preparing the composite activated carbon include 60-80wt% coconut shell fiber powder, 10-18wt% attapulgite clay and 8-25wt% modified wood fossil powder.

2. The composite adsorption catalyst for removing sulfur dioxide from flue gas according to claim 1, characterized in that: The modified petrified wood powder is obtained by subjecting the petrified wood powder to swelling and etherification treatments.

3. The composite adsorption catalyst for removing sulfur dioxide from flue gas according to claim 1, characterized in that: The alkaline auxiliary filler is selected from one or more of fly ash, mica powder, feldspar powder and slaked lime.

4. The composite adsorption catalyst for removing sulfur dioxide from flue gas according to claim 1, characterized in that: The adhesive is selected from one or more of polyvinyl alcohol, polypropylene, and carboxymethyl cellulose.

5. A process for preparing a composite adsorption catalyst for removing sulfur dioxide from flue gas as claimed in any one of claims 1 to 4, characterized in that the steps include: S1, preparing modified wood fossil powder, and then taking dry coconut fiber powder, attapulgite clay, and modified wood fossil powder in proportion and mixing them evenly with a high-speed mixer to obtain a mixture, and taking the mixture and granulating, carbonizing, and activating it to obtain composite activated carbon; S2, taking the composite activated carbon and subjecting it to nitrogen plasma treatment to obtain modified activated carbon; S3, taking the modified activated carbon, alkaline auxiliary filler and adhesive in proportion and mixing them evenly with a high-speed stirrer to obtain a catalyst initial material; S4, taking the catalyst raw material, performing compression molding, drying, sintering, natural cooling, and packaging to obtain a composite adsorption catalyst.

6. The preparation process of the composite adsorption catalyst for removing sulfur dioxide from flue gas according to claim 5, characterized in that: In step S1, the preparation method of the modified wood fossil powder is: (1) Swelling treatment: Take petrified wood powder and disperse it in a polyethylene glycol aqueous solution with a concentration of 0.5-2 mg / mL and a mass of 5-8 times, control the temperature to 50-60°C, and react at a stirring rate of 20-40 r / min for 6-12 hours. After the reaction is completed, filter and wash and dry the petrified wood powder obtained by filtration; (2) Etherification treatment: Take the petrified wood powder after swelling treatment, disperse it in a sodium hydroxide aqueous solution with a mass fraction of 5-8 times and 10-15%, control the temperature to 70-80°C, then add sodium chloroacetate with a mass fraction of 3-6% of the petrified wood powder for reaction for 3-5 hours, adjust the pH to neutral with acetic acid after the reaction is completed, filter, take the filtered petrified wood powder, wash and dry, and obtain the modified petrified wood powder.

7. The preparation process of the composite adsorption catalyst for removing sulfur dioxide from flue gas according to claim 5, characterized in that: In step S1, the granulation refers to using a granulator to form particles of 1-3 mm, the carbonization refers to carbonization at 500-600° C. in a carbonization furnace for 1-2 hours, and the activation refers to activation at 800-1000° C. in an activation furnace for 8-16 hours.

8. The preparation process of the composite adsorption catalyst for removing sulfur dioxide from flue gas according to claim 5, characterized in that: In step S2, the discharge voltage of the nitrogen plasma treatment is 10 kV-30 kV, the treatment time is 20-40 min, and the flow rate of the source nitrogen is 60-100 sccm.

9. The preparation process of the composite adsorption catalyst for removing sulfur dioxide from flue gas according to claim 5, characterized in that: In step S4, the sintering refers to controlling the heating rate of 2-3°C / min in a sintering furnace under an inert atmosphere to raise the temperature in the furnace to 200-250°C, and keeping the temperature for 1-2h.

Citation Information

Patent Citations

  • Surface nitrogen-rich activated carbon and preparation method and application thereof

    CN105921106A

  • Diatomite and activated carbon containing composite desulfurizing agent and preparation method thereof

    CN107824160A

  • Modified activated carbon with high specific surface area and preparation method thereof

    CN116812928A

  • Honeycomb-shaped activated carbon material and preparation method thereof

    CN116850958A

  • Activated carbon-based sulfur dioxide adsorbent and preparation process thereof

    CN117942933A